L’esthétique perceptive et l’interprétation des finale littéraires à travers le cliffhanger (le cas du roman « Le Mystère de la chambre jaune » de Gaston Leroux) - Kost, Hanna (2022)
The paper aims to consider the phenomenon of the cliffhanger as one of the narrative techniques for ending a workof art. A cliffhanger involves creating intrigue or intense anticipation of the outcome both in the final part and inindividual episodes of the work. In literary texts, the cliffhanger is presented as a meta-narrative phenomenon, as thewriter offers a multi-vector development of the plot line involving complex situations and conflicts, the causes andsolutions of which are often hidden or unclear. Such plot modeling leads to in uncertainty, a sense of mystery andan emotional climax. It is the reader who must build a hypothetical relationship between the events and charactersdescribed, determining their place and role in the development of the topic, based on textual data, their own readingexperience, associations and perceptual abilities. Thus, a cliffhanger is an integral part of building and resolvingartistic conflicts. In the novel ‘The Secret of the Yellow Room’, it is represented by the actual linguistic and stylisticparameters and extralinguistic characteristics that stimulate the perceptual activity of the reader.
Keywords: cliffhanger; interruption of the story; ending; effect of suspense; narrative tension; sense of curiosity; perceptual activity of the reader